The Incentive Mechanism for Reducing the Obstacles to Digital Transformation - Omar, Belkacem; Farid, Ahmed Khaled; Mohamed, Guerrache; Redhouane, Lammar; Abdesslam, Menacer; Ahmed, Ben khalifa (Journal of Ecohumanism, 2025)
This study aims to provide one of the important links in order to remove the barriers that can stop digital transformation in organizations, especially in the aspect of human behavior, who symbolizes the interaction of human resources with this change, as this aspect of resources remains the concern of the organization and the answer includes stability about the importance of this link, which is the incentives, which is a priority and a basic supporter that line with many studies of this kind because it does not only contribute to adopting a strategy of giving vital and material motivation to the human resource, but also allows digital transformation to overcome the barrier of resistance to change and include it in the circle of digital culture within it.